The Effect Of Dietary Nano-Selenium And Cannabis Seeds On Liver Tissues And Functions In Male Karadi Lambs (Journal of Pharmaceutical Negative Results, 2022)
This study was done to look into the impact of nano-selenium, cannabis seeds in powdered form and a combination of nano-selenium with cannabis seeds on the liver tissue and liver functions and enzymes in Karadi male lambs. The lambs were divided into four groups; each group included five lambs. The first group was considered as a control group. The second group was orally administrated 0.5 mg/kg of fed of nano-selenium, and the third group was orally administrated 250 mg/kg fed of powdered cannabis seeds. The fourth group used both elements (0.5 mg/kg body weight and 250 mg/kg fed) of nano-selenium and powdered cannabis seeds, respectively. The treatment groups were administrated daily orally for 60 days. To determine the impact of nano-selenium and cannabis seeds on liver tissue and function, tests for alkaline phosphatase, glutamic oxaloacetic transaminase, and glutamic pyruvic transaminase (ALP, GOT, and GPT), serum lipid profile includes (cholesterol, triglyceride, LDL, HDL and VLDL), serum total protein, albumin, andglobulin, as well as liver histopathology, were conducted. The level of serum total protein and albumin were not significantly changed; however, the level of globulin was altered significantly (p<0.05) in the nano-selenium group compared to the control group. Cannabis seeds and nano-selenium with cannabis seeds had significant alteration effects on serum total protein and globulin levels (p<0.01) and (p<0.05), respectively. Cannabis seeds showed a significantly increasing effect on the albumin level (p<0.05). The cholesterol level decreased significantly in the nano-selenium group compared to the control group (p<0.05). The level of cholesterol, Triglyceride, LDL and VLDL was significantly decreased in the cannabis seeds group (p<0.01), but was no statistically changed in HDL level.Serum lipid profile was significantly decreased (p<0.01) in nano-selenium with cannabis seeds groups compared to the control group. ALP was decreased significantly in all treated groups compared to the control group (p<0.01). Liver tissue was shown a protective effect of cannabis seeds as there was no evidence of necrosis, apoptosis and hepatic architectural change; however, the effect of nanoselenium showed no sign of fibrosis, necrosis, neoplasia, or dysplasia, but apoptosis was shown. In contrast, AST was decreased significantly in the nano-selenium group (p<0.05) and in the cannabis seeds treated group (p<0.01), but the level of ALT was not changed significantly in any treated groups. This finding can conclude that the size and dosage of nano-selenium used in the present study are safe for liver tissue as well as have a good impact on increasing the immune system as globulin was increased. Whole cannabis seeds in powdered form have a remarkable impact on liver tissue protection, decreasing lipid profile, increasing protein metabolism by increasing total protein and albumin and boosting the immune system via alteration of globulin.